Phytochemical Investigation In vitro Antioxidant Activity & Anti Diabetic Activity of Euphorbia Nivulia (Journal of Pharmaceutical Negative Results, 2022)
Diabetes is one of the primary causes of mortality. In diabetics, free radicals can cause glucose tolerance, β-cell dysfunction, insulin resistance, decreased macrovascular and microvascular function, and other symptoms. Plant extracts can be efficient treatments because they include a variety of secondary metabolites with distinct medicinal characteristics. As a result, in our research, Euphorbia Nivulia (E. nivulia) is assessed for phytochemical contents, anti-oxidant activity (DPPH test, Superoxide and Nitric oxide scavenging activity), and anti-diabetic activity (α-Amylase Inhibition assay and α-Glucosidase assay). Furthermore, the plant is extracted successively with Ethyl acetate, Petroleum ether and Ethanol. The ethanolic extract produced the highest yield of E. nivulia. Thus, E. nivulia's anti-oxidant and anti-diabetic properties may be beneficial due to the synergistic effects of phytochemicals present in it.